THE INFLUENCE OF FINANCIAL LITERACY ON THE USE OF QRIS AS A PAYMENT METHOD - Mansyur, Muthmainnah; Idris, Abdi Akbar; Nurman; Ramli, Anwar; Aslam, Annisa Paramaswary (Journal Management & Economics Review (JUMPER), 2023)
This research aims to determine the influence of Financial Literacy on the Use of QRIS as a Payment Method among Students of the Management Program, Faculty of Economics and Business, University State of Makassar, batch 2020-2022. The data used in this research is primary data from 135 samples. The methods used to analyze the relationship between independent and dependent variables include descriptive analysis, assumption tests, validity tests, reliability tests, and simple linear regression analysis. The findings in this research show that Financial Literacy (X) affects the Use of QRIS (Y), with a p-value of 0.000 < 0.05, a correlation coefficient of 0.661, and an R Square value of 0.437, which indicates that financial literacy affects the use of QRIS by 43.7%. The regression coefficient value for Financial Literacy (X) is 0.833, meaning that any increase in Financial Literacy leads to an increase in the variable of QRIS Usage. This result is consistent with (H1), which states that Financial Literacy influences the Use of QRIS as a Payment Method among Students of the Management Study Program, Faculty of Economics and Business, Makassar State University.